QUALITY OF LIFE IMPAIRMENTS IN HUNTINGTON’S DISEASE (LITERATURE REVIEW AND OWN DATA) - Usmanov Firdavs Bakhtiyorovich (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract: Huntington’s disease (HD) is a rare, incurable, hereditary neurological disorder that causes the progressive breakdown of nerve cells in the brain. Huntington’s chorea is a progressive neurodegenerative hereditary disorder that is transmitted from generation to generation in an autosomal dominant manner. Huntington’s chorea occurs in 4-6 cases per 100,000 population (4-6:100,000). The classic symptom is chorea, which is the appearance of hyperkinesis, i.e. uncontrolled movements. This is one of the main features of the disease, which is considered to be the anticipation phenomenon, i.e. the disease progresses gradually and begins at a young age [1]. The mutant huntingtin gene has a repeat of the trinucleotide sequence CAG from 40 to 80. The pathogenesis of HD is multifaceted and involves glutamine aggregation, mitochondrial and oxidative stress, mitochondrial-related pathway dysfunction, and DNA damage. Currently, two drugs, tetrabenazine and deutetrabenazine, are approved for the treatment of HD.